Synthesis of various carbon nanomaterials (CNMs) on powdered activated carbon - Al-Saadi, Mohammed A.; Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Alam, Md Zahangir; Sopyan, Iis; Atieh, Muataz A.; Ahmed, Yehya M. (Academic Journals, 2011)
Carbon nanomaterials (CNMs) are promising in many potential applications for their attractive physical and chemical properties. Chemical vapor deposition technique (CVD) is used to synthesize CNMs on fixed substrate. Powdered activated carbon (PAC) was used as a successful substrate for CNMs growth in CVD reaction process. Iron clustered nano particles Fe3+ was impregnated successfully on PAC surface under sonication. EDX characterization results showed the evidence of impregnation and growth of CNMs on PAC surface. The optimum weight percentage of Fe3+ impregnation on PAC was found to be 5%. The CVD reactor used in this study was locally fabricated and modified to reduce the process time and cost. CNMs were synthesized at different temperatures (850, 750, 650 and 550°C) and the maximum yield was obtained at 550°C with majority of CNFs. Various types of CNMs were grown: carbon nanotubes (CNTs), carbon nanofibers (CNFs), CN spheres and CN-coils. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) images were studied for all the samples to investigate the nanostructures for CNMs.